2011
DOI: 10.1097/inf.0b013e3181fe3b5a
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis in Childhood

Abstract: Retrospective evaluation of medical history and 3635 anti-TBE (tick-borne encephalitis) serologies during the years 2003-2008 indicates that childhood TBE is characterized by vague symptoms. Clinical findings suggest a nonspecific inflammatory disease with restricted encephalitic profile compared with adult TBE. Childhood TBE might elude diagnosis, which is unsatisfactory because of potential long-term consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
0
13
0
13
Order By: Relevance
“…EEV in fe ka vus þmo gaus or ga niz mà, su sirg ti EE ga li vi sø am þiaus gru piø at sto vai, ta èiau sirg ti sun kes ne li gos for ma yra la biau ti kë ti na vy res nio am þiaus þmo nëms [9]. Ty ri mai taip pat ro do, kad EE daþ nai ne diag no zuo ja mas vai kams dël ne ið reikð tø simp to mø [15].…”
Section: Klinikaunclassified
“…EEV in fe ka vus þmo gaus or ga niz mà, su sirg ti EE ga li vi sø am þiaus gru piø at sto vai, ta èiau sirg ti sun kes ne li gos for ma yra la biau ti kë ti na vy res nio am þiaus þmo nëms [9]. Ty ri mai taip pat ro do, kad EE daþ nai ne diag no zuo ja mas vai kams dël ne ið reikð tø simp to mø [15].…”
Section: Klinikaunclassified
“…Die FSME verläuft bei Kindern und Jugendlichen häufig unspezifisch mit den Symptomen eines grippalen Infektes und somit gutartiger [20,21]. In den letzten Jahren häufen sich jedoch auch Berichte über langwierige neurologische Funktionsstörungen bei Kindern [11, 22 -34].…”
Section: Leitsymptomeunclassified
“…Two recent studies from Sweden showed that TBE in children can present also as a nonspecific inflammatory disease with a restricted encephalitic profile compared to adults making the diagnosis difficult in selected cases [17,19].…”
Section: Introductionmentioning
confidence: 99%